Nuclear Spin Singlet States in Photoactive Molecules: From Fluorescence/NMR Bimodality to a Bimolecular Switch for Spin Singlet States. Issue 9 (28th January 2019) - Yang, Shengjun; McCormick, Jeffrey; Mamone, Salvatore; Bouchard, Louis‐S.; Glöggler, Stefan
Abstract: Nuclear spin singlet states are silent states in nuclear magnetic resonance (NMR). However, they can be probed indirectly and offer great potential for the development of contrast agents for magnetic resonance imaging (MRI). Introduced here are two novel concepts: Firstly, the bimodal NMR/fluorescence properties of 13 C2 ‐tetraphenylethylene. It possesses a long‐lived singlet state in organic solvents, and it shortens upon the addition of water. This simultaneously increases the aggregation‐induced emission (AIE) of the molecule, resulting in a substantial enhancement of fluorescence. Secondly, introduced is a bimolecular switch for singlet states based on 3‐ 2 H ‐coumarin containing an isolated proton. Upon UV‐light exposure, a dimer forms, leading to a coupling between two previously isolated protons. A nuclear spin singlet state can now be populated. Excitation with a wavelength of 254 nm results in partial ring cleavage of the molecule back to its monomer. Abstract : Light switch : Two novelties with respect to photoactive molecules are introduced. Described is a bimodal NMR spectroscopy/fluorescence approach to monitor molecules and a bimolecular light switch for nuclear spin singlet states.